2016
DOI: 10.3386/w22630
|View full text |Cite
|
Sign up to set email alerts
|

Student Coaching: How Far Can Technology Go?

Abstract: Recent studies show that programs offering structured, one-on-one coaching and tutoring tend to have large effects on the academic outcomes of both high school and college students. These programs are often costly to implement and difficult to scale, however, calling into question whether making them available to large student populations is feasible. In contrast, interventions that rely on technology to maintain low-touch contact with students can be implemented at large scale and minimal cost but with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…Minimum word counts and time restrictions were imposed to encourage participants to give each answer an appropriate amount of consideration -to encourage students to write freely, we made clear we would delete their written thoughts after emailing their completed exercise for reference. Responses to part of a similar exercise reported in Oreopoulos and Petronijevic (2017) suggest that virtually all students took the task very seriously, writing in personal detail. The entire module was designed to take two hours to complete.…”
Section: Treatmentsmentioning
confidence: 98%
“…Minimum word counts and time restrictions were imposed to encourage participants to give each answer an appropriate amount of consideration -to encourage students to write freely, we made clear we would delete their written thoughts after emailing their completed exercise for reference. Responses to part of a similar exercise reported in Oreopoulos and Petronijevic (2017) suggest that virtually all students took the task very seriously, writing in personal detail. The entire module was designed to take two hours to complete.…”
Section: Treatmentsmentioning
confidence: 98%
“…(At CUNY colleges, the caseload is estimated to be higher.) A fairly robust experimental literature on enhanced academic advising interventions finds positive, although often modest, causal effects on students' academic outcomes using a variety of modes of advising (for examples, see Avery, Howell, and Page 2014;Bailey et al 2016; Barr and Castleman 2017;Bettinger and Baker 2014;Sacerdote 2013, 2017;Evans et al 2017;Oreopoulos and Petronijevic 2016;Scrivener and Weiss 2009).…”
Section: A Background and Barriers To Academic Successmentioning
confidence: 99%
“…There is promising evidence that this approach can succeed at shifting teaching practice and improving student learning (Kraft et al 2018), but it is generally considered more expensive (Knight 2012). Recent evidence has also shown that low-cost adaptations to coaching, such as using online technology, is less effective (Oreopoulos & Petronijevic 2018).…”
Section: Introductionmentioning
confidence: 99%